Occurrence of cetaceans and seabirds along the Indian Ocean 110°E meridian from temperate to tropical waters. (November 2022) - Sprogis, Kate R.; Sutton, Alicia L.; Jenner, Micheline-N.; McCauley, Robert D.; Jenner, K. Curt S.
Abstract: The first extensive physical and biological observations of the Indian Ocean were made from 1959 to 1965, during a ship-based International Indian Ocean Expedition (IIOE-1). Decades later in 2019, the 110°E meridian was revisited during the second International Indian Ocean Expedition (IIOE-2). The aim of this study, as part of a large number of related studies, was to examine the occurrence of cetaceans and seabirds along the 110°E meridian from temperate to tropical waters (39.5–11.5°S). Cetaceans and seabirds were actively scanned for across a four-week period spanning austral autumn to winter. Acoustic recordings of vocalising cetaceans were made using directional and omnidirectional sonobuoys ( n  = 87 deployments). In total, seven cetacean sightings (six baleen whale, one toothed whale), 186 seabird sightings and 225 cetacean acoustic detections were recorded. The baleen whale species detected acoustically were assigned to Antarctic blue whales ( Balaenoptera musculus intermedia ; Z-calls), pygmy blue whales ( B. m. brevicauda ; south east Indian Ocean 3-component calls, D-calls), fin whales ( B. physalus ; 20 Hz-pulses), southern right whales ( Eubalaena australis; upcalls), Antarctic minke whales ( B. bonaerensis ; bio-duck calls) and an unknown signal; a "spot call". The toothed whale species detected acoustically were Kogia sperm whales ( Kogia sp.) and delphinids (from whistles).. Pygmy blue whales were detected across Subantarctic to Tropical Surface Waters, and were the most commonly detected cetacean. There was some delineation in other cetaceans: the spot call was detected in Subantarctic and Subtropical Surface Water (south of 23°S); fin whales in Subtropical Surface Water (between 23° and 30.5°S); and Antarctic minke whales in Tropical Surface Water (between 14° and 23°S). Data were not collected on cetaceans during IIOE-1, so data here represent baseline occurrence along 110°E for future studies. A total of 22 seabird species were sighted, including, petrels, albatrosses, tropicbirds, terns, shearwaters, boobies, frigatebirds, gannets, gulls, skuas and prions. Soft-plumaged petrels ( Pterodroma mollis ) were observed across all water masses and were the most commonly sighted seabird. There was some delineation of seabird species; albatrosses were sighted south of the Subtropical Front (south of 32°S); flesh-footed shearwaters ( Ardenna carneipes ) in Subantarctic and Subtropical Surface Waters (south of 27°S); and tropicbirds in Tropical Surface Water (north of 20°S). The occurrence of highly mobile species is particularly important to investigate as the waters in the eastern Indian Ocean have been warming faster than in the Pacific and Atlantic Oceans. Highlights: 242 acoustic detections of cetaceans and 186 seabird sightings were recorded. Fin whales in subtropical waters, Antarctic minke whales in tropical waters. Albatrosses, prions and shearwaters in temperate waters, tropicbirds in the tropics. Pygmy blue whales and soft-plumaged petrels ubiquitous across water masses.